2015
DOI: 10.1111/1751-2980.12283
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in patients with intestinal malabsorption syndromes – think in and outside the gut

Abstract: There is a very high prevalence of vitamin D deficiency, which is defined by a serum level of 25-hydroxyvitamin D [25(OH)D] of lower than 20 ng/mL, in all populations of the world. Unfortunately, the prevalence of vitamin D deficiency in patients with intestinal malabsorption syndromes, including cystic fibrosis (CF), celiac disease (CD), short bowel syndrome and inflammatory bowel disease (IBD), is higher than that in the general population, indicating the presence of disease-specific causative factors. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 208 publications
(309 reference statements)
1
48
0
7
Order By: Relevance
“…48 Vitamin D 3 exerts its antioxidant functions also by affecting the antioxidant enzymes. 49 Our study showed a decreased serum activity of GPx3 in the study groups with reduced serum vitamin D 3 levels. Inflammation with overexpressed tumor necrosis factor α may lead to reducing serum vitamin D 3 levels, and on the other hand, reduced concentrations of vitamin D 3 seem to be one of the causes leading to the impairment of antioxidant defense.…”
Section: Ståhlberg Et Alsupporting
confidence: 49%
“…48 Vitamin D 3 exerts its antioxidant functions also by affecting the antioxidant enzymes. 49 Our study showed a decreased serum activity of GPx3 in the study groups with reduced serum vitamin D 3 levels. Inflammation with overexpressed tumor necrosis factor α may lead to reducing serum vitamin D 3 levels, and on the other hand, reduced concentrations of vitamin D 3 seem to be one of the causes leading to the impairment of antioxidant defense.…”
Section: Ståhlberg Et Alsupporting
confidence: 49%
“…VD decrease in these patients is the result of several factors, such as a reduced absorption of lipidsoluble vitamins, a greater inflammationmediated extrarenal expression of CYP27B1, and hyperparathyroidism secondary to hypocalcemia in some patients; this leads to a greater 25(OH)D conversion into 1,25(OH)2D and, therefore, lower 25(OH)D levels. 34 Cystic fibrosis and VDD: The prevalence of an inadequate VD status in patients with CF may be as high as 95%. 35 Ninety percent of the CF population have pancreatic insufficiency, which causes malabsorption of fat and, therefore, lipid-soluble vitamins, including VD.…”
Section: Vitamin D Deficiency In Pediatric Clinical Practice / E77mentioning
confidence: 99%
“…La disminución de VD en estos pacientes se debe a varios factores, tales como la disminución de absorción de vitaminas liposolubles y la mayor expresión extrarrenal de CYP27B1 mediada por la inflamación y el hiperparatiroidismo secundario a la hipocalcemia en algunos pacientes; esto lleva a una mayor conversión de 25(OH)D en 1,25(OH) 2 D y, por tanto, a unas concentraciones de 25(OH)D más bajas. 34 FQ y DVD: La prevalencia de un estado inadecuado de VD en pacientes con FQ puede llegar a ser tan alta como el 95%. 35 El 90% de la población que padece FQ tiene insuficiencia pancreática, la cual lleva a malabsorción de grasas y, con ello, de vitaminas liposolubles, como la VD.…”
Section: Asmaunclassified